т.А(1;1;1), т.B(x;y). Вектор AB(x-1;y-1;0-1).Вектор a(1;2;3).Составим уравнения, используя условие коллинеарности:(x-1) / 1 = (y-1) / 2 = (0-1) / 3.Решим уравнения:(x-1) / 1 = (0-1) / 3; x-1 = -1/3; x = (3/3)-(1/3) = 2/3.(y-1) / 2 = (0-1) / 3; y-1 = (-1/3)*2; y = (3/3) - (2/3) = 1/3.ответ: Вектор AB(-1/3;-2/3;-1).
т.А(1;1;1), т.B(x;y). Вектор AB(x-1;y-1;0-1).
Вектор a(1;2;3).
Составим уравнения, используя условие коллинеарности:
(x-1) / 1 = (y-1) / 2 = (0-1) / 3.
Решим уравнения:
(x-1) / 1 = (0-1) / 3; x-1 = -1/3; x = (3/3)-(1/3) = 2/3.
(y-1) / 2 = (0-1) / 3; y-1 = (-1/3)*2; y = (3/3) - (2/3) = 1/3.
ответ: Вектор AB(-1/3;-2/3;-1).